(untitled) (Actual Problems of Psychology in Educational Institutions, 2018)
The article marks the main tendencies of reforming modern education. The author emphasizes the reorientation school teaching of foreign languages into communicative-activity, person-oriented and cultural trends, outlines the principles of English language teaching in primary schools in the system «The New Ukrainian School».